2016
DOI: 10.1007/s12105-016-0695-8
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Sinonasal Round Cell Undifferentiated Tumors

Abstract: The sinonasal cavities host a wide variety of undifferentiated malignancies with round cell morphology, including neoplasms of epithelial, mesenchymal, neuroectodermal, and hematolymphoid lineage. The differential diagnosis may be difficult, especially in small biopsy material, due to overlapping morphology, but their correct classification is clinically relevant. The aim of this review is to provide practical guidelines for the differential diagnosis of these malignancies, with emphasis on recently described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…However, the tumor cells exhibited positive expression of epithelial markers, including EMA and pan-cytokeratin. These characteristics mimic those of undifferentiated nasopharyngeal carcinomas that occur commonly in sinonasal regions (14). However, characteristically, undifferentiated nasopharyngeal carcinomas exhibit cytokeratin 5, p63 and p40 expression (15), which was not exhibited by the tissue analyzed in the present study.…”
Section: Discussionsupporting
confidence: 65%
“…However, the tumor cells exhibited positive expression of epithelial markers, including EMA and pan-cytokeratin. These characteristics mimic those of undifferentiated nasopharyngeal carcinomas that occur commonly in sinonasal regions (14). However, characteristically, undifferentiated nasopharyngeal carcinomas exhibit cytokeratin 5, p63 and p40 expression (15), which was not exhibited by the tissue analyzed in the present study.…”
Section: Discussionsupporting
confidence: 65%
“…The 2017 World Health Organization (WHO) classification of head and neck tumours has defined SNUC as a highly aggressive tumour of uncertain histogenesis without evidence of squamous or glandular differentiation 1 thus representing a category with a diagnosis of exclusion. Some evidence for neuroendocrine differentiation in SNUC has been reported 5 , 6 , but most authors do not classify them as neuroendocrine neoplasms for the lack of neuroendocrine immunoreactivity 7 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Documenting mitotic activity is important, because in presence of similar immunoreactivity, SCC-NET is distinguished from moderately differentiated neuroendocrine tumor (atypical carcinoids) based on mitotic count. 9,10 In the study, SCC-NETs were found immune-reactive with pan-cytokeratins and neuroendocrine markers usually CD56. Variable immunoreactivity was seen with synaptophysin and chromogranin (Figure 1).…”
Section: Epithelial Srcts Of the Sinonasal Area 411 Sinonasal Undiffe...mentioning
confidence: 86%